Hands-on RESTful web API design patterns and best practices : design, develop, and deploy highly adaptable, scalable, and secure RESTful web APIs /: design, develop, and deploy highly adaptable, scalable, and secure RESTful web APIs. (2019) - Subramanian, Harihara; Raj, Pethuru
No abstract available